Antioxidant and organoleptic test of Soursop (Annona muricata Linn.) leaf tea in herbal tea production process - Tria Syafa’atun; Nur Marisa (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2020)
Soursop leaves (Annona muricata Linn.) contain antioxidant compounds. Antioxidants are useful for protecting body cells from damage caused by free radicals. The purpose of this study was to analyze the antioxidant and organoleptic activity of soursop leaf herbal tea (Annona muricata Linn.). The antioxidant activity test used the DPPH method (2,2-diphenyil-1-picrylhydrazyl), while the organoleptic test was performed using the scoring method. The results of the study stated that the highest taste value was obtained in the 150-minute drying time sample of 2.4 and the lowest value in the 60-minute drying time sample of 2.1. The highest color was obtained in the sample drying time of 60 minutes of 3.5, while the lowest value of the sample of drying time of 150 minutes was 1.8. The highest aroma value was obtained in the 60-minute drying time sample of 3.2 and the lowest aroma value in the 120-minute drying time sample of 2.2.©2020 JNSMR UIN Walisongo. All rights reserved.